RocTest: A standardized method to assess the performance of root organ cultures in the propagation of arbuscular mycorrhizal fungi - Goh, Dane; Martin, Julien G. A.; Banchini, Claudia; MacLean, Allyson M.; Stefani, Franck (Frontiers in Microbiology, 2022)
Over the past three decades, root organ cultures (ROCs) have been the gold standard method for studying arbuscular mycorrhizal fungi (AMF) under in vitro conditions, and ROCs derived from various plant species have been used as hosts for AM monoxenic cultures. While there is compelling evidence that host identity can significantly modify AMF fitness, there is currently no standardized methodology to assess the performance of ROCs in the propagation of their fungal symbionts. We describe RocTest, a robust methodological approach that models the propagation of AMF in symbiosis with ROCs. The development of extraradical fungal structures and the pattern of sporulation are modelled using cumulative link mixed models and linear mixed models. We demonstrate functionality of RocTest by evaluating the performance of three species of ROCs (Daucus carota, Medicago truncatula, Nicotiana benthamiana) in the propagation of three species of AMF (Rhizophagus clarus, R. irregularis, Glomus sp.). RocTest produces a simple graphical output to assess the performance of ROCs and shows that fungal propagation depends on the three-way interaction between ROC, AMF, and time. RocTest makes it possible to identify the best combination of host / AMF for fungal development and spore production, making it an important asset for germplasm collections and AMF research.